Development blind spot detector of automobile - Zulfadli Azri Asmadi
This final year project is about development blind spot detector of automobile which involves two major parts. First part involves a survey on an awareness of blind spot phenomena among Malaysian drivers and the second part is to investigate by experiments a blind spot area and angle that suit for average Malaysian driver's based on body size.